Investigation of the Effects of Needle Designs on the Root Canal Irrigation Using Computational Fluid Dynamics - Bulgu, Selin; Yıldızeli, Alperen; Çadırcı, Sertaç; Yıldırım, Sema (Deu Muhendislik Fakultesi Fen ve Muhendislik, 2023)
This study aims to investigate the effects of irrigation needles geometries on the flow inside the root canal and compare their irrigation performances based on Computational Fluid Dynamics (CFD) analyzes. CFD simulations of three commonly used close-ended irrigation needles were performed for various inlet Reynolds numbers and working lengths. Their irrigation performances were evaluated based on apical pressure and wall shear stress. The flow was assumed to be incompressible, turbulent and steady at all inlet Reynolds numbers. The closed-ended needles showed similar limited irrigant penetration toward the apex. Among all configurations, the Model C outperforms others as it provides the highest wall shear stress around the needle tip and the lowest apical pressures in the apical foramen, which reduces the risk of apical extrusion. The needle tip designs influence important parameters for the effectiveness and safety of the irrigation process.
Keywords: Hesaplamalı Akışkanlar Dinamiği (HAD); Endodonti; İrigasyon; İğne Ucu Tasarımı; Computational Fluid Dynamics (CFD); Endodontics; Irrigation; Needle Tip Design; Computational Methods in Fluid Flow, Heat and Mass Transfer (Incl. Computational Fluid Dynamics); Akışkan Akışı, Isı ve Kütle Transferinde Hesaplamalı Yöntemler (Hesaplamalı Akışkanlar Dinamiği Dahil)